Analisis Rasio Likuiditas, Rasio Solvabilitas dan Rasio Profitabilitas untuk Mengukur Kinerja Keuangan PT Kimia Farma Tbk Periode 2015-2024 - Ficky Fakhrizati Diani; Aria Aji Priyanto (Lembaga Yasin AlSys, 2026)
The instability of PT Kimia Farma Tbk’s financial performance, as reflected in fluctuations in financial ratios and several ratios that were below industry standards, indicates the need for a comprehensive evaluation of the company’s financial condition. This study aims to analyze the financial performance of PT Kimia Farma Tbk for the 2015–2024 period through liquidity ratios, solvency ratios, and profitability ratios. This study employed a quantitative descriptive method with analytical techniques in the form of liquidity ratios, solvency ratios, and profitability ratios. The results showed that the company’s financial performance was still not optimal. In terms of liquidity ratios, the current ratio (CR) was in a poor condition with an average of 117.36%, lower than the industry standard of 200%, while the quick ratio (QR) also indicated a poor condition with an average of 74.57%, below the industry standard of 150%. In terms of solvency ratios, the debt to asset ratio (DAR) of 58.88% was above the industry standard of 35%, and the debt to equity ratio (DER) of 156.90% exceeded the industry standard of 90%, thus indicating an unfavorable condition. Meanwhile, in terms of profitability ratios, the net profit margin (NPM) indicated a poor condition with an average of -0.84%, far below the industry standard of 20%. Thus, the financial performance of PT Kimia Farma Tbk for the 2015–2024 period can be considered not yet optimal. This study has implications as evaluation material for the company in formulating improvement measures to enhance its financial performance.